Effect of postural changes on in vivo pelvic tilt and functional component anteversion in total hip arthroplasty patients with lumbar disc degenerations. (2nd November 2020) - Klemt, Christian; Limmahakhun, Sakkadech; Bounajem, Georges; Xiong, Liang; Yeo, Ingwon; Kwon, Young-Min
Abstract : Aims: The complex relationship between acetabular component position and spinopelvic mobility in patients following total hip arthroplasty (THA) renders it difficult to optimize acetabular component positioning. Mobility of the normal lumbar spine during postural changes results in alterations in pelvic tilt (PT) to maintain the sagittal balance in each posture and, as a consequence, markedly changes the functional component anteversion (FCA). This study aimed to investigate the in vivo association of lumbar degenerative disc disease (DDD) with the PT angle and with FCA during postural changes in THA patients. Methods: A total of 50 patients with unilateral THA underwent CT imaging for radiological evaluation of presence and severity of lumbar DDD. In all, 18 patients with lumbar DDD were compared to 32 patients without lumbar DDD. In vivo PT and FCA, and the magnitudes of changes (ΔPT; ΔFCA) during supine, standing, swing-phase, and stance-phase positions were measured using a validated dual fluoroscopic imaging system. Results: PT, FCA, ΔPT, and ΔFCA were significantly correlated with the severity of lumbar DDD. Patients with severe lumbar DDD showed marked differences in PT with changes in posture; there was an anterior tilt (-16.6° vs -12.3°, p = 0.047) in the supine position, but a posterior tilt in an upright posture (1.0° vs -3.6°, p = 0.005). A significant decrease in ΔFCA during stand-to-swing (8.6° vs 12.8°, p = 0.038) and stand-to-stance (7.3° vs 10.6°, p = 0.042) was observed in the severe lumbar DDD group. Conclusion: There were marked differences in the relationship between PT and posture in patients with severe lumbar DDD compared with healthy controls. Clinical decision-making should consider the relationship between PT and FCA in order to reduce the risk of impingement at large ranges of motion in THA patients with lumbar DDD.